Sarcopenia as a risk factor of morbimortality in colorectal cancer surgery - Pereira, Mariana (2020)
Background: Colorectal cancer (CRC) surgery is associated with high rates of postoperative morbimortality. Sarcopenia has been identified as an independent predictor of these surgical outcomes. Methods: A sample of 272 patients who underwent CRC surgery between January 2005 and May 2010 at Braga Hospital, was selected. Sarcopenia was defined by the skeletal muscle mass index, measured by preoperative computed tomography (CT), at L3 level, using ImageJ® software. Associations between sarcopenia and qualitative variables were analyzed by Chi-Square Test (χ2) or Fisher’s Exact Test and, for quantitative variables, by Mann-Whitney Test. A multivariate logistic regression was performed to assess if sarcopenia was an independent predictor of major morbidity. The overall and recurrence-free survivals were analyzed by Kaplan-Meier method and multivariate Cox regression was performed for recurrence-free survival. Results: The prevalence of sarcopenia was 19.1%. Sarcopenia was associated with male gender, no CRC family history and colon tumour (p < 0.001, p = 0.029 and p = 0.017, respectively). The presence of sarcopenia was associated with postoperative morbidity Clavien–Dindo classification (p = 0.003), and sarcopenia was an independent predictor for major complications (grade ≥ III) (p = 0.003). Conclusions: The evaluation of sarcopenia in patients undergoing CRC surgical resection allows to predict a higher probability of major postoperative morbimortality.